Sistem Informasi Reservasi Bagi Pengunjung Destinasi Wisata Gua Limbuhang Haliau - Muhammad Rifaldi Rahman; Mursid Dwi Hastomo; Haderiansyah Haderiansyah (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The reservation information system facilitates online booking of products or services, eliminating manual reservations through phone or email. Gua Limbuhang Haliau is still using manual data recording by hand, which is susceptible to errors and makes data analysis difficult. This research aims to develop a web-based online reservation system for Gua Limbuhang Haliau using the System Development Life Cycle (SDLC) method and PHP programming language with MySQL database. This system enables visitors to make reservations and access via the internet to monitor daily, weekly, monthly, and even yearly visits. The qualitative model used is descriptive narrative to explain the process of developing the reservation information system in detail.